Sigmoid Volvulus; Frequency of Postoperative Complications of Primary Repair - Anayat Ullah Safi, Khawar Iqbal, Mohammad Shoaib Khan, Farah Saleem, Umair Tahir Chaudary, Muhammad Attique Sadiq (Pakistan Journal of Medical & Health Sciences, 2022)
Many regions of the world, including Pakistan, are affected by sigmoid volvulus, which is the most prevalent cause of major gut obstruction. The ingestion of high-fibre bulky foods, which seem to overburden the sigmoid colon, are two of the most common causes of sigmoid volvulus, along with irregular bowl habits. The most common clinical manifestations are abdominal discomfort, distension, constipation, nausea, and vomiting. The surgery of preference is resection and primary anastomosis since it avoids the need for a colostomy and the following reversal. Objectives: The goal of this study was to investigate the prevalence of postoperative complications after primary surgery in individuals with viable or gangrenous sigmoid volvulus. Place and Duration: This descriptive research was done in the surgical department of Sheikh Khalifa Bin Zaid Hospital (PGMI), Quetta and Fauji Foundation Hospital Rawalpindi for the duration of six months from January 2021 to June 2021. Methodology: The researchers looked at patients who had a large gut obstruction and were suspected of having sigmoid volvulus based on clinical and radiographic evidence. In these individuals, laparotomy and sigmoid colon resection were done, followed by single-layer primary anastomosis to restore colon continuity. A total of 90 individuals were included in the research after informed consent. Results: This research covered a total of 90 patients. With a male to female ratio of 2.5:1, there were 63 (70%) men and 27 (30%) females. Patients varied in age from 35 to 70 years old. The mean age of the patients was 50 + 1.30 years. The majority of the patients were between the ages of 41 and 45. All 90 patients (100%) had stomach discomfort, which was predominantly on the left side, followed by constipation in 84 (93.3 percent) and abdominal distension in 81 (90 percent). In 12 (13.3 percent) of the patients, vomiting was present, and in 3 (3.3 percent) of the patients, bleeding per rectum (due to related haemorrhoids) was evident. In 23 (25.6%) of the cases, various post-operative problems developed. Wound infection was found in 12 (13.3%) of the cases, with 9 men and three females being admitted to the hospital for antibiotics and daily dressings until the wounds healed. All of the wounds healed well. Pelvic abscess occurred in 4 (4.4%) of the patients. Three patients (3.3%) developed an enterocutaneous fistula, which was managed conservatively until the fistula healed. Only one patient (one percent) had ileus Conclusion: When the gut is viable or gangrenous, resection with primary anastomosis is the best treatment option for sigmoid volvulus.